Pre-service English teachers’ perceptions of their online teaching practice during pandemic times - Aguilar-Cruz, Paola Julie (2021)
This paper investigates pre-service English teachers’ perceptions on their online teaching practice during pandemic times, focusing on issues related to technology, materials development and gamification. Accordingly, a qualitative narrative research approach was implemented to deeply inquiry pre-service English teachers through interviews and artifacts. It is concluded that even though pre-service English teachers had to face different concerns related to their online teaching practice, such as students’ lack of commitment, low motivation and connectivity issues because of the pandemic, still they were capable of understanding and reflecting upon their role as teachers and used technology and gamified activities to overcome their concerns.